The Impact of e-Health Literacy on Health Promotion Behaviors of High School Students - Kübra Pınar Gürkan; Dijle Ayar (Galenos Yayinevi, 2020)
Aim:The aim of this study was to investigate the effects of e-health literacy on health promotion behaviors on high school students.Materials and Methods:This descriptive, cross-sectional and relational study was conducted between May-June 2019 in a high school chosen by a random sampling method from the high schools of Narlıdere District of İzmir Province. Data were collected using a descriptive information form, the e-Health Literacy scale in Adolescents and the Adolescent Health Promotion scale. The data collected from the study was analyzed using numbers, percentages, average, Pearson correlation analysis and regression analysis in SPSS 22.0.Results:57.1% of the students included in this study were male and their mean age was 16.52±0.92 years. It was found that 47% of the students were studying in the 10th grade. Of the students' mothers, 42.1% were primary school graduates, while 29.2% of the fathers were primary school graduates. It was determined that 95% of the students used the internet, 69.4% accessed the internet via mobile phone and 65.3% did not take health promotion lessons at school. It was also seen that there was a positive moderate relationship between the e-health literacy and mean Health Promotion scale scores of the high school students, and that 17% of the factors affecting adolescent health promotion behaviors were explained by the total e-health literacy mean scores (r=0.416; p<0.001).Conclusion:It was found that there was a statistically significant relationship between e-health literacy and the health promotion behaviors of the students, but it was found that the total score means of health promotion behaviors were not at the desired level. Starting from an early period, it is recommended to conduct interventional studies aimed at increasing health promotion behaviors in children and adolescents.